2019
DOI: 10.30658/jicrcr.2.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Posts on Samsung Galaxy Note 7 Explosion: A Comparative Analysis of Crisis Framing and Sentiments in Three Nations

Abstract: This study explores the Samsung Galaxy Note 7 explosion crisis by analyzing posts on Twitter in three nations: the United States, Australia, and South Korea. Using the perspectives of generic frames, issue-specific frames, cross-national frames, and user sentiment on Twitter, this study analyzes 600 posts (200 from each nation). Results reveal that Twitter posts frequently framed the crisis using attribution, morality, and conflict frames. Posts about the explosion were more professional frame oriented than na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Sentiment analysishashtag and emoji. Sentiment analysis is used to measure the positive, negative, or neutral feelings of users of social media platforms towards communication around a certain topic, 26 which in our study concerns the experience of Long Covid during the Covid-19 pandemic. Emoji and hashtag analysis was conducted through the interpretation of co-occurrence, frequency and discourse analysis (with the software Talkwalker) which involved examining hashtags and emojis within the context of their posts.…”
Section: Discussionmentioning
confidence: 99%
“…Sentiment analysishashtag and emoji. Sentiment analysis is used to measure the positive, negative, or neutral feelings of users of social media platforms towards communication around a certain topic, 26 which in our study concerns the experience of Long Covid during the Covid-19 pandemic. Emoji and hashtag analysis was conducted through the interpretation of co-occurrence, frequency and discourse analysis (with the software Talkwalker) which involved examining hashtags and emojis within the context of their posts.…”
Section: Discussionmentioning
confidence: 99%
“…Even if an individual experiences negative emotions and low organization reputation in both cases, they could be triggered to share negative WOM when the responsibility (and, therefore, blame) of the organization is clearly identified. In preventable crises, stakeholders would particularly be able to identify the organization to blame, and the complaints would likely increase since the organization is an easy target (Kang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Each party also needs to make predictions about what the other party expects regarding the negotiation outcome. Kang et al (2019), in their study on the exploded Samsung Note 7 phone, mentioned the negotiation strategies implemented by Samsung by determining customers' expectations of the company's reaction to the issue. During the ground rules phase, the parties involved will define their ground rules and the procedures that will be taken to conduct the negotiation process.…”
Section: Process Of Negotiationmentioning
confidence: 99%
“…The negotiation process should also be appropriately conducted to ensure the needs and demands of the parties involved can be addressed. Kang et al (2019) examined the crisis of the Samsung Galaxy Note 7 explosion by analyzing posts from the social media platforms Twitter regarding the issue. The study revealed that the users often complained about the strategies that should have been taken by Samsung during the pre-crisis phase and critiqued the value of attribution and morality.…”
Section: Process Of Negotiationmentioning
confidence: 99%
See 1 more Smart Citation